A ideia do infinito e do desejo metafísico como saída da filosofia da imanência em Levinas - Santos, Joseildo Inácio dos (2024)
The many armed conflicts, internal or between nations, that humanity has gone through throughout its history, bringing with them violence, catastrophe and suffering, disturb man's desire to understand their meaning. It was driven by this same concern that, in the 20th century, the Franco-Lithuanian philosopher Emmanuel Levinas developed a hermeneutics of war, addressing its immediate and harmful effects. Where he notices not only the existence of a similarity between the totalitarian and violent power typical of states of war and the way of thinking of the Philosophical Tradition in its ontological bias, but also the point that the phenomenon of war has its foundation in this violent way of thinking of Western rationality. As a result, it denounces ontology as the philosophy of power and violence, as well as accusing modern subjectivity as ratifying the violent process of totalization and immanentization of Reality. However, Emmanuel Levinas speaks in favor of transcendence, by understanding the Other as the Infinite and in benefit of the ethical relationship, which is the metaphysical movement, where the finite Self moves from its interiority to the exteriority manifested by the Other, in a Metaphysical Desire where there is no possibility of immanentization, since the Other, being infinite, is an unavoidable horizon, closed to the Rational process of apprehension, but open to ethical encounter.